2008
DOI: 10.3844/ajabssp.2008.706.711
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Farmers Willingness to Pay for Wheat Consultant Engineers Project: In Iran

Abstract: Problem statement: Public extension performance in many developing countries including Iran is not up to the expectation of farming community. Further, in recent years, many governments are very reluctant to shoulder huge financial investment for public extension. Hence, extension specialists and policy makers propose privatization of extension services in developing countries. Approach: Considering existing agricultural extension scenario, a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Several studies in Iran showed that, although extension services has played a positive role in agricultural development of Iran [22] , but there are difficulties, barriers, misunderstandings and weaknesses in the transfer of new technology and information to farmers. Lacking the suitable extension organizational characteristics has been a barrier for transfer of appropriate new technology to farmers [8] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in Iran showed that, although extension services has played a positive role in agricultural development of Iran [22] , but there are difficulties, barriers, misunderstandings and weaknesses in the transfer of new technology and information to farmers. Lacking the suitable extension organizational characteristics has been a barrier for transfer of appropriate new technology to farmers [8] .…”
Section: Resultsmentioning
confidence: 99%
“…Organic food is perceived to be better than traditionally grown food, which is the reason why health is often a primary consideration in purchasing decisions (Pearson, 2001;Chinnici et al, 2002;Hill and Lynchehaun, 2002;Tregear et al, 1994). However, inflated prices are often cited as one of the significant barriers to purchasing (Asadi et al, 2008;Millock et al, 2002;Nedra et al, 2015;Lee and Yun, 2015), and between 2000 and 2013, as many as 194 research studies have addressed this issue (R€ odiger and Hamm, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, the perception of these products is a result of knowledge concerning organic products. Numerous researches were also carried out, particularly on the consumer's perception of the price which is considered more expensive than that of the conventional products (Govindasarny and Italia, 1999;Sanchez et al, 1998;Boccaletti and Nardella, 2000;Gil et al, 2001;Millock et al, 2002;Brugarolos Mollà-Bauzà et al, 2005;Asadi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%